Can arterial wave augmentation in young adults help account for variability of cardiovascular risk in different British ethnic groups?. Issue 11 (November 2016) - Faconti, Luca; Silva, Maria J.; Molaodi, Oarabile R.; Enayat, Zinat E.; Cassidy, Aidan; Karamanos, Alexis; Nanino, Elisa; Read, Ursula M.; Dall, Philippa; Stansfield, Ben; Harding, Seeromanie; Cruickshank, Kennedy J.
Abstract : Objective: Traditional cardiovascular risk factors do not fully account for ethnic differences in cardiovascular disease. We tested if arterial function indices, particularly augmentation index (AIx), and their determinants from childhood could underlie such ethnic variability among young British adults in the 'DASH' longitudinal study. Methods: DASH, athttp://dash.sphsu.mrc.ac.uk/, includes representative samples of six main British ethnic groups. Pulse wave velocity (PWV) and AIx were recorded using the Arteriograph device at ages 21–23 years in a subsample ( n = 666); psychosocial, anthropometric, and blood pressure (BP) measures were collected then and in two previous surveys at ages 11–13 years and 14–16 years. For n = 334, physical activity was measured over 5 days (ActivPal). Results: Unadjusted values and regression models for PWVs were similar or lower in ethnic minority than in White UK young adults, whereas AIx was higher – Caribbean (14.9, 95% confidence interval 12.3–17.0%), West African (15.3, 12.9–17.7%), Indian (15.1, 13.0–17.2%), and Pakistani/Bangladeshi (15.7, 13.7–17.7%), compared with White UK (11.9, 10.2–13.6%). In multivariate models, adjusted for sex, central SBP, height, and heart rate, Indian and Pakistani/Bangladeshi young adults had higher AIx (β = 3.35, 4.20, respectively, P < 0.01) than White UK with a similar trend for West Africans and Caribbeans but not statistically significant. Unlike PWV, physical activity, psychosocial or deprivation measures were not associated with AIx, with borderline associations from brachial BP but no other childhood variables. Conclusion: Early adult AIx, but not arterial stiffness, may be a useful tool for testing components of excess cardiovascular risk in some ethnic minority groups.